Perkembangan Hukum Islam Masa Kini di Negara ASEAN - Fauzi Salim, Rahmad; Fuad, Zainul (Rayah Al-Islam, 2023)
Perkembangan hukum Islam di berbagai negara sangat pesat, tidak hanya di negara-negara timur tetapi negara-negara di Asia Tenggara juga menerapkan hukum Islam dalam peraturan negaranya. Negara-negara di Asia Tenggara membentuk organisasi yang disebut ASEAN. Terkait penerapan syariat Islam di negara-negara ASEAN juga tidak terlepas dari kontroversi antara umat Islam dengan agama lain di berbagai negara ASEAN. Kajian ini mengkaji perkembangan hukum Islam saat ini di negara-negara ASEAN. Kajian ini berfokus pada penerapan hukum Islam di negara-negara ASEAN yang bertujuan untuk mengetahui bagaimana perkembangan hukum Islam di negara-negara ASEAN. Penelitian ini menggunakan metode penelitian yuridis normatif dan menggunakan buku dan artikel serta jurnal yang berkaitan dengan hukum Islam di negara-negara ASEAN. Hasil dari penelitian ini adalah tidak semua negara di ASEAN dapat menerapkan hukum Islam secara penuh dalam peraturan negaranya, seperti Singapura, Myanmar dan Thailand. Namun, ada beberapa negara yang mengakui dan menerapkan syariat Islam dalam peraturan negaranya, seperti Indonesia dan Malaysia serta Brunei Darussalam. The development of Islamic law in various countries is very rapid, not only in eastern countries but countries in Southeast Asia also apply Islamic law in their state regulations. Countries in Southeast Asia formed an organization called ASEAN. Regarding the application of Islamic law in ASEAN countries, it is also inseparable from the controversy between Muslims and other religions in various ASEAN countries. This study examines the current development of Islamic law in ASEAN countries. This study focuses on the application of Islamic law in ASEAN countries which aims to find out how the development of Islamic law in ASEAN countries. This research uses normative juridical research methods and uses books and articles and journals related to Islamic law in ASEAN countries. The results of this study are not all countries in ASEAN can fully implement Islamic law in their country regulations, such as Singapore, Myanmar and Thailand. However, there are several countries that recognize and apply Islamic law in their state regulations, such as Indonesia and Malaysia and Brunei Darussalam.